A classical time integration method applied for solution of nonlinear equations of a double-layer tensegrity - Greco, Marcelo; Ferreira, Ivone Passos; Barros, Felício Bruzzi (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2013)
The paper aims to investigate the nonlinear geometrical behavior of a tensegrity structure subject to dynamic loading in the time domain. The geometric nonlinearity is considered here with the aid of a simple set of equations, based on the Finite Element Method, but using nodal positions rather than nodal displacements as variables. The finite element strains are evaluated directly from the proposed position concept, using a coordinate system fixed in space. The performance of two transient direct integration algorithms was implemented, one explicit and another implicit, considering the eventual inclusion of a numerical damping in the positional formulation. The algorithmic numerical damping is especially interesting for analyses during long time periods or for unstable slender structures. The dynamical behavior of a double-layer tensegrity system is analyzed using the time integration algorithms developed in the paper. Results point to the importance of the numerical damping in the analysis and the mechanical behavior dependence of the initial strain level prescribed in the cables. The development of classical time integration schemes for the positional formulation is original and the application for the double-layer tensegrity proves the accuracy of the method.